Uang Elektronik dalam Perspektif Maqasid al-Shari’ah al-Syatibi - Pangestu, Zakaria Adjie (Maliyah : Jurnal Hukum Bisnis Islam, 2023)
The currencies used by humans to transact change. Initially relying on barter, then using dinars and dirhams, changing to using cash, to the latest update to Electronic Money or e-money, originating from the human mind that continues innovating with technological advances to facilitate activities and life. E-money offers practicality in transactions. Its significant influence on society and the economy of a country, especially Indonesia, raises the need to solve problems related to Sharia views on e-money. Islamic law is a rule/regulation that prioritises the benefit of humankind. This research answers questions related to the suitability of electronic money with the concept of maqāṣid al-sharī’ah al-Syatibi. This research uses qualitative research. The data source comes from the literature examining al-Syatibi's maqāṣid al-sharī’ah and electronic money, with data collection techniques that take objects from documents. In this research, the documents are in the form of al-Muwāfaqāt fi uṣul al-shari’ah, Bank Indonesia Regulation number 16/8/PBI/2014, and DSN-MUI fatwa number 116/DSN-MUI/IX/2017. The e-money concept follows the principle of hifẓu al-māl/safeguarding property and the maintenance of property at the al-hājiyat level. Because e-money facilitates human transactions, it does not interfere with life even if it is not fulfilled. However, it can complicate the efficiency of activities if not used. E-money follows the relevant fikih  muamalah contracts and is free from forbidden elements, namely maysir/gambling, gharar, and usury. On the other hand, unregistered electronic money does not fulfil the principle of hifẓu al-māl, so it can cause harm when used.